FAKTOR PERSONAL YANG BERHUBUNGAN DENGAN KOMITMEN ORGANISASI PERAWAT RSUD EMBUNG FATIMAH BATAM - Nahrul Hayat; asfri sri rahmadeni; Isna Aglusi Badri; Dermawan Sidabutar (HUMAN CARE JOURNAL, 2020)
Commitment is the attitude or behavior of likes or dislikes shown by someone against the organization at work. Indonesia is recorded as a nurse who has a low organizational commitment (76%) so it harms services. This phenomenon in the hospital can be seen from the indicator of the high turnover rate of nurses which reaches 30.9% which exceeds the standard <5%. Many factors affect organizational commitment. The purpose of this study was to analyze the Personal Factors Associated with Organizational Commitment of Hospital Nurses. This study is a cross-sectional analytic study and purposive sampling technique with a sample of 59 nurses. Chi-Square test results obtained personal factors that have a relationship with organizational commitment Nurse Hospital is age with p = 0,000 and education with p = 0,000, personal factors not related to organizational commitment are gender p = 1,053 and years of service with p = 1,147. Hospitals should conduct research/surveys on Organizational Commitment periodically as an evaluation material in the context of the organization's development and development in the future.